Analysing Homosexual Identity Development in E.M. Forster’s Maurice: A Study from the Perspective of the Cass Identity Model - Sadaf Ashraf Talpur; Muhammad Tufail Chandio; Sanaullah Rustamani (University of Chitral Journal of Linguistics and Literature, 2024)
The undertaken research aims to analyse the homosexual identity development of an Edwardian gentleman named Maurice Hall depicted in E.M. Forster’s novel ‘Maurice’. The qualitative data has been reviewed from the text of the novel to analyse the homosexual identity development in the protagonist of the novel from the vantage point of the six-staged Cass identity model (1979) based on identity confusion, identity comparison, identity tolerance, identity acceptance, identity pride, and identity synthesis. The model further elucidates identity foreclosure, which is failure to complete any of these stages and stagnate the process of identity development. It has been found that Maurice Hall deems himself undesirable until he makes peace with his sexual identity by passing through each step of the Cass Identity Model.